О РЕДАКТОРСКОЙ И АВТОРСКОЙ МИСТИФИКАЦИЯХ: ПУБЛИКАЦИЯ РОМАНА МЫ В «ВОЛЕ РОССИИ» - Vinokurov, Fjodor (Przegląd Rusycystyczny, 2016)
ON EDITOR ’S AND AUT HOR ’S MYSTIFIC ATIONS : PU BLIC ATION OF NOVEL WE IN MAGAZINE “VOLI A ROSSII ” S u m m a r y Evgeny Zamiatin’s novel WE has a notable publishing history. In 1927 exile magazine “Volia Rossii” (Freedom of Russia) for the first time published in Russian “extracts” from the novel, which were pretended to be retranslation back into Russian from Czech newspaper version. For the effect of retranslation forced corruptions were carried in original Russian text. Literary editor Marc Slonim later stated that he was forced to use this subterfuge for author’s safety. According to Zamiatin’s version magazine made this publication without his permission and against his prohibition. In actual fact evidences of both sides are a mystification. Comparison of publication in magazine with typescript and lifetime published translations of the novel shows that it appears to be a magazine’s montage-version created by editorial board based on author’s manuscript with minimal use of translations, and amount of “editor’s corruptions” there is inappreciable.